Nursing of a patient with bullous pemphigoid complicated with hydrocephalus and respiratory disorders (1例大疱性类天疱疮合并脑积水并发呼吸障碍患者的护理体会) - ZHANG Ying (张莹) (Association of Integrative Nursing, 2022)
This paper summarized the nursing management for a patient with bullous pemphigoid complicated with hydrocephalus and respiratory disorders. Based on the nursing risk assessment, comprehensive nursing measures of integrated traditional Chinese and western medicine were carried out to enhance the nutrition status, skin care, psychological health of the patient, in order to relieve the symptoms of bullous pemphigoid and improve the outcomes of the patient. (本文总结1例大疱性类天疱疮合并脑积水并发呼吸障碍患者的护理经验。通过科学的护理评估, 明确护理目标, 开展中西医结合护理, 同时做好皮肤护理, 加强饮食和心理干预, 促进患者疱疹好转, 改善预后。)